Taboo guessing game / Ainul Hafizah Hisyam - Hisyam, Ainul Hafizah (Academy of Language Studies, 2023)
Later, a guessing board game called Taboo was played as their activity of the day. The rules were thoroughly explained by me before they started playing it for 30 minutes. At the end of the class, the most words were managed to be gotten by group 3. On Tuesday, July 4, the focus was on verbal expression. Students were asked to write their own words on paper after being introduced to "quotes." I provided examples in my own words and shared them with the class, along with tips on effective idea conveyance. The paper was folded into a paper plane by them when everyone had done writing on it as I had told them. The paper plane was then launched into the air by them, making a mess on the ground that could be picked up by anybody and read quietly to themselves.